The Influence of Fundamental and Macroeconomic Factors on Stock Returns in Building Construction Companies Listed on the Indonesian Stock Exchange for the 2018-2022 Period - Sugianto, Ahmad; Riyanti, Riyanti; Hakim, Luqman (Journal of World Science, 2024)
This research focuses on analyzing the impact of fundamental and macroeconomic factors on stock returns within the building construction sector of companies listed on the Indonesia Stock Exchange during the period from 2018 to 2022. Employing a quantitative, associative approach, the study encompasses a population of 25 building construction companies, with a purposive sampling method narrowing it down to 14 companies. The research employs multiple linear regression analysis using IBM SPSS Statistics 26 software as the analytical tool. The findings reveal that the Return on Equity Ratio (ROE) and Debt to Equity Ratio (DER) exert a negative and significant influence on stock returns. Furthermore, economic growth (GDP) demonstrates a positive and significant impact, while inflation and interest rates exhibit a negative and insignificant effect on stock returns. Collectively, these factors, including ROE, DER, GDP, inflation, and interest rates, collectively exert a significant influence on stock returns. The implications of these findings underscore the importance of considering these factors for investors, policymakers, and practitioners in the building construction industry.